Costa Rica : Technical Assistance Report-The Coordinated Direct Investment Survey and the Coordinated Portfolio Investment Survey (March 6-14, 2014). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission about the Coordinated Direct Investment Survey and Coordinated Portfolio Investment Survey in Costa Rica. It was observed that the practices followed to prepare external statistics employed adequate data collection instruments and appropriate methodologies. The mission stresses the importance of defining and implementing, in the short term, a work program to convert the complete balance of payments and International Investment Position historical series using the sixth edition of the Balance of Payments and International Investment Position Manual (BPM6) presentation. The conversion of time series to BPM6 should be accompanied by a methodological note explaining the characteristics of the new series and specifying which data were estimated in accordance with the new classification.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet